PENGARUH ROLE CONFLICT, ROLE AMBIGUITY, DAN ROLE OVERLOAD TERHADAP CYBERLOAFING DENGAN EMOTIONAL INTELLIGENCE SEBAGAI VARIABEL PEMODERASI - Rikha Muftia Khoirunnisa; Candra Vionela Merdiana (Optimum: Jurnal Ekonomi dan Pembangunan, 2019)
The internet helps organizations/companies achieve their goals more effectively and efficiently, both in terms of costs, energy, and time. On the one hand, these facilities support the achievement of company goals. But on the other hand, these facilities will cause problems if employees cannot use them optimally to help complete their work. The phenomenon of using internet facilities in the workplace for purposes not related to work is known as cyberloafing. This study examined the direct effect of role conflict, role ambiguity, role overload, and emotional intelligence on cyberloafing, then examined the role of moderating emotional intelligence on the influence of role conflict and role ambiguity on cyberloafing. The respondents of this study were employees (civil servants) of the Department of Education, Youth and Sports in DIY. The sample in this study was taken using a purposive sampling method. Hypothesis testing uses multiple regression. The results showed that role conflict and emotional intelligence proved to be influential on cyberloafing. Emotional intelligence has also been shown to moderate the influence of role conflict on cyberloafing. Whereas role ambiguity and role overload have not been proven to influence cyberloafing. Likewise, the role of moderating emotional intelligence on the influence of role ambiguity on cyberloafing is also not proven.Â Keywords: role conflict, role ambiguity, role overload, kecerdasan emosional, cyberloafing